Software for automation of measurements with Keysight E4980a LCR meter = Oprogramowanie automatyzujące pomiary wykonywane miernikiem RCL Keysight E4980a - Malinowski, Maciej; Kampik, Marian; Musioł, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents software dedicated for automatic impedance measurements performed using Keysight E4980A precision LCR meter. The software has been written in Microsoft Office Excel Visual Basic for Applications (VBA) and is very useful for automated determination of impedance frequency characteristics and for plotting them in Microsoft Excel.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne